2019
DOI: 10.17816/ecogen17221-34
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the congruence between morphogenetic and molecular-genetic modules of gray voles Microtus S.L. variability along a climatic gradient

Abstract: Background. The exponential growth of research concerning a role of morphological modularity and integration in evolution has taking place from the beginning of the century. It was especially noted that inter-level integration should manifest itself, first of all, in the congruent variability of the modules of different structural levels. We analyzed congruence between the interspecific variability of the first lower molar (m1) masticatory surface and the mtDNA Cytb gene in ten species of the gray voles Microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
3
0
1
Order By: Relevance
“…Asymmetry is also common; e.g. in 10 species of Arvicolini, Kovaleva et al (2019) found 27.7% of individuals with an asymmetric M1. The molars assume an adult pattern early in postnatal ontogenesis, e.g.…”
Section: Dentitionmentioning
confidence: 99%
“…Asymmetry is also common; e.g. in 10 species of Arvicolini, Kovaleva et al (2019) found 27.7% of individuals with an asymmetric M1. The molars assume an adult pattern early in postnatal ontogenesis, e.g.…”
Section: Dentitionmentioning
confidence: 99%
“…Package JACOBI4 is freely available at [w1]. There are also articles available [3,22] in which JACOBI4 is used to process real biological data, as well as supplemental files containing JACOBI4 scripts and data for them.…”
Section: Resultsmentioning
confidence: 99%
“…Для статистического сравнения аспектов ДМФ у студентов использовался PLS-анализ (метод частичных наименьших квадратов для получения проекций на латентные структуры). Инструментом PLS-анализа являются бикомпонентные модели (2B-PLS, Two-Block PLS) (Rohlf, Corti 2000), которые наиболее эффективны для изучения имплицитных психофизиологических процессов через выявление глубинных «латентных структур» (Kovaleva et al 2019;Nikolaeva et al 2022).…”
Section: материалы и методыunclassified